CONSCIENCE IN THE LIGHT OF PSYCHOLOGICAL THEORIES - Srampickal, Thomas (Asian Horizons, 2016)
Conscience was almost exclusively a subject matter of religion, theology and philosophy. But in recent times we have realized that it is too complex to be neatly contained in speculative disciplines alone. It demands interdisciplinary approach and studies. This article discusses moral development and conscience formation in the light of the findings of psychological researches. Though there are several approaches/theories in this field, we have chosen what are considered to be major ones as well as representative. They are identification theory, cognitive-developmental approach, behaviourism and character study. Each theory has its own conception of conscience, its characteristics, formative factors and process — conscience involves affective/empathic, cognitive and behavioural dimensions, all of which need to be integrated into a mature character. Though the various theories presented here appear quite diverse they are at the same time complementary.